2021
DOI: 10.1186/s12890-021-01425-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel association between asthma and osteoarthritis: a nationwide health and nutrition examination survey

Abstract: Background Asthma and osteoarthritis (OA) are medical conditions that inhibit physical activity and adversely affect quality of life. Despite the high prevalence, there are limited studies focusing on the comorbid condition and association between asthma and OA. The aim of this study was to assess the prevalence of OA co-occurring with asthma and to identify the relevant clinical considerations. Methods Adult participants aged over 40 years who com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
5
8
0
Order By: Relevance
“…Bronchial asthma often presents with chest pain or discomfort [ 61 ]. This result is consistent with the high incidence of pain related conditions such as osteoarthritis in patients with asthma [ 62 ]. Chronic activation of immune cells in damaged tissues (i.e., inflammation) is known to cause hypersensitivity of peripheral pain-sensing neurons by several mechanisms [ 63 ].…”
Section: Discussionsupporting
confidence: 88%
“…Bronchial asthma often presents with chest pain or discomfort [ 61 ]. This result is consistent with the high incidence of pain related conditions such as osteoarthritis in patients with asthma [ 62 ]. Chronic activation of immune cells in damaged tissues (i.e., inflammation) is known to cause hypersensitivity of peripheral pain-sensing neurons by several mechanisms [ 63 ].…”
Section: Discussionsupporting
confidence: 88%
“…In support of our results, prior work has shown an increased prevalence of OA in patients with asthma compared with patients with COPD and control patients 33. This prior study was limited by a small sample size, which included 425 patients with asthma (135 with OA) and 1131 patients with COPD (201 with OA).…”
Section: Discussionsupporting
confidence: 84%
“…Data from German Health Update demonstrated that the OA incidence was significantly higher in individuals with asthma compared with those without asthma, and the increased risk remained significant even after adjusted for age group, gender, BMI, educational attainment, and smoking status [ 40 ]. The above result was supported by another nationwide survey [ 41 ]. However, MR studies found that asthma did not show a causal effect on OA [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 65%